Pola Pemahaman Kebencanaan dan Mitigasi Bencana di Kalangan Siswa SD Negeri 1 Peukan Bada, Aceh Besar - Muhammad Hafiz Daniel; Uswatun Nisa; Muhammad Saleh Sjafei (Universitas Teuku Umar, 2024)
Peukan Bada, situated near the North Sea in Aceh, was severely affected by the 2004 Aceh tsunami incident. This is the basis for the construction of the evacuation building shelter and first tsunami research center in Aceh, the Tsunami, Disaster, and Mitigation Research Center (TDMRC) in Peukan Bada, 2006. Peukan Bada, one of the areas affected by the tsunami incident, is also a destination for socialization sessions about disaster orientation and mitigation for local citizens. The intended socialization has been carried out in SD Negeri 1 Peukan Bada by Syiah Kuala University students majoring in Communication Studies. The method is carried out through a participatory method that focuses on reciprocal interaction between presenters and participants. Result: This dedication demonstrates that primary students' understanding of disaster and mitigation prior to socialization remains relatively common. The students were given knowledge about disaster and fire disaster mitigation tips and also earthquakes; messages and knowledge materials were delivered in an interesting way and communicative because it was accompanied by children’s games that train students’ concentration and courage to speak. This activity is organized using the participative method, so hopefully it can be a medium of disaster introduction and mitigation tips for students in SD Negeri 1 Peukan Bada.